The Influence of Corporate Social Responsibility on Financial Performance: Study of Family Business in Central Java - Marchyta, Nony Kezia; Arijanto, Kezia Virelia (Jurnal Aplikasi Bisnis dan Manajemen, 2023)
This research aims to analyze the relationship between corporate social responsibility (CSR), family commitment, and financial performance in the family business in Central Java. This research is quantitative, with the data tested using Structural Equation Model - Partial Least Square. The population of this research is family businesses in Central Java. The sample of this research was determined using the purposive sampling technique. The data were collected using questionnaires distributed using Google Forms; 86 respondents answered the questionnaires and met the criteria for the research. This research indicates that family commitment positively influences both CSR and financial performance; CSR also positively influences financial performance, which means CSR partially mediates the relation between family commitment and financial performance. Furthermore, the research shows that CSR benefits are not limited to non-family businesses but also family businesses in developing countries. Therefore, family businesses must commit themselves to CSR as it will increase their reputation and trust among stakeholders who are competitive advantages culminating in better financial performance. Keywords: corporate social responsibility, family commitment, financial performance, family business, developing country